2004
DOI: 10.1080/00140130310001617967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of precision demands and mental pressure on muscle activation and hand forces in computer mouse tasks

Abstract: The objective of the present study was to gain insight into the effects of precision demands and mental pressure on the load of the upper extremity. Two computer mouse tasks were used: an aiming and a tracking task. Upper extremity loading was operationalized as the myo-electric activity of the wrist flexor and extensor and of the trapezius descendens muscles and the applied grip-and click-forces on the computer mouse. Performance measures, reflecting the accuracy in both tasks and the clicking rate in the aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
79
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 32 publications
10
79
1
3
Order By: Relevance
“…On the other hand, another group of researchers found that the existence of a certain psychosocial stress did not have any significant effect on trapezius muscle activity [9,14,18,19,23,24,27,28]. Meanwhile, there are several studies that can be categorized in a third group where this group obtained a combination of the two aforementioned results [1,25,26,29].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, another group of researchers found that the existence of a certain psychosocial stress did not have any significant effect on trapezius muscle activity [9,14,18,19,23,24,27,28]. Meanwhile, there are several studies that can be categorized in a third group where this group obtained a combination of the two aforementioned results [1,25,26,29].…”
Section: Discussionmentioning
confidence: 98%
“…Even for the most common muscle studied which is the trapezius muscle, the effect of stress on muscle activity can be divided into two main groups. One group found that when a certain psychosocial stress exists, the trapezius muscle will become affected and the muscle activity will be increased significantly [8,12,18,21,[29][30][31]35]. On the other hand, another group of researchers found that the existence of a certain psychosocial stress did not have any significant effect on trapezius muscle activity [9,14,18,19,23,24,27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of similar studies, in which mental stress was induced amongst computer users in a laboratory setting, support these findings (Lundberg et al, 2001). A recent study investigating the possible effects of mental pressure and demands for precision on upper extremities found a considerable increase in the load as a result of mental pressure (Visser et al 2004). Another study, which investigated the effects of time pressure and precision demands on the oxygen of two muscles, m. trapezius and m. extensor carpi radialis, found reductions in oxygenation of the latter during a mouse-operated computer task carried out und time pressure and high precision demands (Heiden et al, 2005).…”
mentioning
confidence: 68%
“…3-4 hours) can result in fatigue of the forearm muscles (Johnson, 1998 (Wahlstrom et al, 2002). It w further supported by the results of another study, which explored effects of mental pressure on precision and on the force applied when working with the computer mouse (Visser et al, 2004). P S and neck/upper extremity symptoms during computer work (Bergqvist et al, 1995;Faucett and Rempel, 1994;Karlqvist et al, 2002;Punnett and Bergqvist, 1997;Tittiranonda et al, 1999).…”
mentioning
confidence: 78%